Photonuclear production of F-18 - Dikiy, N.P.; Dovbnya, A.N.; Krasnoselsky, N.V.; Lyashko, Yu.V.; Medvedeva, E.P.; Medvedev, D.V.; Uvarov, V.L.; Fedorets, I.D. (Вопросы атомной науки и техники, 2018)
¹⁸F is one of the most important positron emitters which are routinely used in the positron emission tomography (PET). The recoil nuclei method in the ¹⁹F(Ɣ,n)¹⁸F reaction was used for the production of ¹⁸F free carrier. The sufficiently high energy of recoil nuclei in this reaction can be up to 200 keV. The mixture of 180 nanometer CaF₂ nanoparticles and an acceptor in the form of a nanoparticle of food salt was irradiated with bremsstrahlung with a maximum energy of 13.5 MeV. Irradiated samples were placed in distilled water to dissolve the sodium chloride. The yield of the ¹⁸F isotope in the solution was 30.2% of the total activity of the sample. The estimation of the ¹⁸F production on an electron accelerator with a power of 10 kW and an energy of 35 MeV can be up to 1 Ci for 4 hours.